The effects of Islamic education teachers' readiness in teaching sexual health elements - Ihwani, Siti Suhaila (Politeknik Nilai Negeri Sembilan, 2016)
Teachers’ readiness in teaching is crucial in producing and creating effective teaching methods, especially towards the mastery, practices among secondary school teachers. Therefore, this paper discusses a study of the Malaysian teachers’ readiness in teaching the sex education elements based on four aspects which are personality, knowledge, skills and attitudes. A set of questionnaire was used as the research instrument to evaluate the level of the teachers’ readiness who were respondents of this study. The data was analyzed using the IBM SPSS Statistic (Predictive Analytic Software) version 23 in a descriptive manner using the frequency of mean, percentage and standard deviation. The result of the descriptive analysis showed that the level of the respondents readiness was intermediate (mean=4.70; sd=0.74). and their level of readiness in teaching sexual education elements was at a high level. The inference analysis utilized the t-test and the One-way Analysis of Variance (ANOVA). The t-test and ANOVA were utilized to identify the significant differences upon the respondents’ level of readiness based on school’s location, gender, academic qualification and teaching experience.